Research on the Species Diversity and Distribution Patterns of Wild Ribes in Northeast Asia - Ximing Zhao; Dandan Zhao; Xinrui Ge; Yin Zhang; Yuxiao Du; Jingguo Liu; Yuning Liu; Hongfeng Wang; Baojiang Zheng (Plants)
Ribes is the only genus in the Grossulariaceae family and holds considerable economic importance. Northeast Asia represents one of the major global centers of Ribes distribution. This study presents the first comprehensive investigation focused on this region, examining the diversity, distribution patterns, and environmental determinants of wild Ribes species through field surveys and a review of the relevant literature. Results indicate the presence of 36 species (including 8 varieties) from 7 subgenera of wild Ribes across Northeast Asia, predominantly belonging to the subgenera Berisia, Ribes, and Grossularia. The species are unevenly distributed throughout the region: (1) The Russian Far East exhibits the highest species richness, with 21 species from 5 subgenera, followed by Northeast China (16 species, 6 subgenera), Japan (12 species, 7 subgenera), Mongolia (10 species, 3 subgenera), South Korea (9 species, 5 subgenera), and North Korea (8 species, 5 subgenera). These findings suggest that the Russian Far East currently serves as the core distribution center for Ribes in Northeast Asia. (2) The species diversity of wild Ribes exhibits a unimodal latitudinal pattern, peaking between 47° N and 52° N. (3) A similar unimodal trend is evident along altitudinal gradients, with most species occurring between 500 m and 1500 m. (4) Species richness is primarily influenced by temperature stability and extreme low temperatures, followed by precipitation seasonality and elevation, while annual precipitation shows a relatively minor effect. This study offers crucial baseline data for the conservation and sustainable utilization of Ribes in Northeast Asia.